The Positive Association between Plasma Myristic Acid and ApoCIII Concentrations in Cardiovascular Disease Patients Is Supported by the Effects of Myristic Acid in HepG2 Cells. Issue 10 (25th July 2020) - Olivieri, Oliviero; Speziali, Giulia; Castagna, Annalisa; Pattini, Patrizia; Udali, Silvia; Pizzolo, Francesca; Liesinger, Laura; Gindlhuber, Juergen; Tomin, Tamara; Schittmayer, Matthias; Birner-Gruenberger, Ruth; Cecconi, Daniela; et al.
ABSTRACT: Background: In the settings of primary and secondary prevention for coronary artery disease (CAD), a crucial role is played by some key molecules involved in triglyceride (TG) metabolism, such as ApoCIII. Fatty acid (FA) intake is well recognized as a main determinant of plasma lipids, including plasma TG concentration. Objectives: The aim was to investigate the possible relations between the intakes of different FAs, estimated by their plasma concentrations, and circulating amounts of ApoCIII. Methods: Plasma samples were obtained from 1370 subjects with or without angiographically demonstrated CAD (mean ± SD age: 60.6 ± 11.0 y; males: 75.8%; BMI: 25.9 ± 4.6 kg/m 2 ; CAD: 73.3%). Plasma lipid, ApoCIII, and FA concentrations were measured. Data were analyzed by regression models adjusted for FAs and other potential confounders, such as sex, age, BMI, diabetes, smoking, and lipid-lowering therapies. The in vitro effects of FAs were tested by incubating HepG2 hepatoma cells with increasing concentrations of selected FAs, and the mRNA and protein contents in the cells were quantified by real-time RT-PCR and LC-MS/MS analyses. Results: Among all the analyzed FAs, myristic acid (14:0) showed the most robust correlations with both TGs ( R = 0.441, P = 2.6 × 10 −66 ) and ApoCIII ( R = 0.327, P = 1.1 × 10 −31 ). By multiple regression analysis, myristic acid was the best predictor of both plasma TG and ApoCIII variability. Plasma TG and ApoCIII concentrations increased progressively at increasing concentrations of myristic acid, independently of CAD diagnosis and gender. Consistent with these data, in the in vitro experiments, an ∼2-fold increase in the expression levels of the ApoCIII mRNA and protein was observed after incubation with 250 μM myristic acid. A weaker effect (∼30% increase) was observed for palmitic acid, whereas incubation with oleic acid did not affect ApoCIII protein or gene expression. Conclusions: Plasma myristic acid is associated with increased ApoCIII concentrations in cardiovascular patients. In vitro experiments indicated that myristic acid stimulates ApoCIII expression in HepG2 cells.